Bereavement care practices following stillbirths: Health-care provider's perspective - Bharti Sharma; Shatakshi Kulshreshtha; Neelam Aggarwal; Vanita Suri; Ritu Nehra (Wolters Kluwer Medknow Publications, 2022)
Background: Addressing stillbirth is a difficult task and becomes more challenging with a huge burden and skewed doctorpatient ratio. There is a lack of data regarding the knowledge about the bereavement care practices following pregnancy loss and practices being followed by the health-care providers in the Indian context. The objective of this study is to describe the experience, views, and practices of health-care professionals while managing women with stillbirths. Design: Internet-based Monkey Survey. Methodology: An on-line self completion questionnaire was shared with various health care providers via emails and whats app groups. Results: A total of 281 responses of health-care providers were analyzed, and the majority of them were obstetricians. Almost 90% had managed women with stillbirth, but just a third (38.1%) had provided bereavement care. The majority of them felt the lack of a uniform and comprehensive training model for providing bereavement care to such women. Out of 281 participants, 258 (91.8%) believed that health-care providers should have a bereavement care training and support system, whereas only 23 (8.2%) rejected this idea. Conclusion: There is no defined protocol or standards for providing bereavement care to women following stillbirth. Most health-care professionals feel an urgent need for professional training to bridge the gap between the expectations of patients and the care provided.